Factors affecting parental satisfaction after male circumcision - Reyaz Ahmad Wani; Bilal Yousuf Mir (Journal of Indian Association of Pediatric Surgeons, 2023)
Background: The safety of the male circumcision depends on many factors, including the surgeon, type of anesthesia, and associated complications. The scientific knowledge regarding safe MC is not so prevalent among masses. Aims and Objectives: To study the level of awareness regarding circumcision amongst parents and highlight factors linked to parental satisfaction. Materials and Methods: Information regarding various factors was gathered with the help of structured questionnaire-based evaluation of parental knowledge and experience. This was followed by clinical examination by a pediatric surgeon for assessment of cosmetic outcome, complications and need for additional surgical procedure. Results: Most circumcisions were performed by non-surgeons beyond neonatal period. Majority of the procedures were done under local anesthesia and around 17% procedures were done by quacks without anesthesia. More than 20% parents were dissatisfied with the procedure. Around 80% parents considered perioperative period mildly to moderately stressful. The overall complication rates were higher than usual with need for surgical correction in more than 40% patients. Conclusion: There is lack of awareness regarding safe MC practices in general public. MC by inexperienced people contributes to higher complication rates and need for redo, which in turn is related to parental dissatisfaction.